POLA ASUH ORANG TUA TERHADAP KEPERCAYAAN DIRI PESERTA DIDIK - Rahma Indrimalia, M. Dahlan R, Syarifah Gustiawati (JURNAL PENELITIAN PENDIDIKAN SOSIAL HUMANIORA, 2020)
Every child development is a complex process, it cannot be formed only from within the child, but also the environment in which the child lives. Parents are the main educators who have different parenting patterns. Parenting is a series of attitudes shown by parents to children to create an emotional climate that covers interactions between children and their parents. Parenting given by parents will affect the child's developmental stage. One factor that is usually affected is self-confidence. If a child has high self-esteem, then the child will be able to live a life and be able to actualize his potential and talents, but conversely if the child has low self-confidence then the child will find many difficulties in living his life in the future. This study aims to determine the relationship of parenting parents with student confidence. This research is a quantitative study and the research method used is a survey research method with data collection techniques such as questionnaires or questionnaires, observations and documentation as well as the research sample of 50 students in class VIII MTsN Bogor. The results of this study indicate that there is a significant correlation value of 0.533, which means 0.533> 0.2732 so that it can be concluded that there is a positive relationship between parenting parents and the self-confidence of class VIII students in MTsN Bogor city with the level of data interpretation including moderate, namely between levels 0.40-0.70.